Stakeholder-based modelling in climate change planning for the agriculture sector in Argentina - Gutman, Verónica; Frank, Federico Carlos; Monjeau, Adrian; Peri, Pablo Luis; Ryan, Daniel; Volante, Jose Norberto; Apaza, Luciana; Scardamaglia, Virginia (Taylor & Francis, 2024)
The development of long-term scenarios to outline pathways for achieving carbon neutrality by 2050 has become a standard practice in climate change policy planning. In Argentina, a modelling process was initiated in 2019 in the agriculture, forestry and other land use (AFOLU) sector utilizing three tools: FABLE calculator, Dinamica EGO and Nature Map. In order to generate technical inputs for the modelling exercise a stakeholder dialogue was launched. A 2050 Carbon Neutrality scenario was developed, alongside several intermediate scenarios based on stakeholders´ visions of the future. The modelling results demonstrated the biophysical feasibility of achieving carbon neutrality in the Argentinean AFOLU sector by 2050. However, alignment with current sectoral priorities was identified as a challenge, leading stakeholders to propose less ambitious scenarios as more attainable targets. This experience underscored the significance of constructing multiple policy scenarios, facilitating the evaluation of diverse potential future trajectories for olicymaking. These different pathways provided contrasting perspectives between political objectives, such as achieving carbon neutrality, and the practical feasibility of local implementation. Moreover, the process highlighted the vital role of integrating the private sector and environmental nongovernmental organizations (NGOs) in long-term climate planning, emphasizing the need for inclusive collaboration to address climate challenges effectively.